Sex Determination on Racing Pigeons (Columba livia) Molecularly Using Blood Samples - Azzahra, Laila Salwa; Srihanto, Eko Agus; Rustiati, Elly Lestari; Master, Jani; Firwantoni, Firwantoni; Febriyani, Dwi Ayu; Pratiwi, Dian Neli (Ann Publisher, 2025)
Background. Pigeons (Columba livia) belong to the Columbidae. Pigeons possess diverse ecological, economic, and aesthetic values, as they are monomorphic, exhibiting similar characteristics between male and female individuals, especially at a young age. Aims. In collaboration with the Lampung Disease Investigation Center, a study has been done to confirm the sex determination of pigeons at a young age by the PCR technique. Blood samples were taken in two locations, East Lampung and Kota Metro. Molecular análisis was carried out at the Biotechnology Laboratory, Lampung Disease Investigation Center. Methods. The technique includes DNA extraction, DNA amplification, electrophoresis and visualization. Result. It poses a significant challenge for pigeon breeders in sex determination. Blood is a source of genetic material that can be used to determine the sex of birds. The Chromo-Helicase-DNA-binding Protein (CHD) gene is one of the genes used as a marker to molecularly differentiate the sex of birds. The sex chromosomes in female individuals have heterozygous chromosomes (ZW) and male individuals have homozygous sex chromosomes (ZZ). Conclusion. Of eleven pigeon blood samples, there were seven female and four male individuals, and there was one mistake in the gender prediction by the pigeon owner